High-Degree AV Block in STEMI with Metabolic Disorders: Who is the Prime Suspect? - Sinulingga, Brigitta Olivia; Sitepu, Andika (Medistra Medical Journal (MMJ), 2025)
Background: ST-elevation myocardial infarction (STEMI) is typically associated with a single culprit lesion. However, cases involving dynamic progression or multiple simultaneous infarct-related arteries are rare but carry significantly higher risks, particularly when accompanied by malignant arrhythmias and electrical instability. Case Illustration: A 33-year-old male, active smoker and casual drinker, presented with acute chest pain, dyspnea, and nausea. He was initially diagnosed with inferior STEMI and transient ventricular tachycardia at the referring hospital. Upon transfer, his ECG evolved to show inferior-anterior STEMI with complete atrioventricular block. Shortly after arrival, he experienced cardiac arrest and was successfully resuscitated. Coronary angiography revealed dual culprit lesions: total occlusion of both the right coronary artery (RCA) and the left anterior descending artery (LAD). PCI was performed with drug-eluting stent placement in the RCA, and balloon angioplasty with thrombus aspiration and intracoronary eptifibatide in the LAD. Revascularization achieved TIMI III flow.Discussion: Despite successful PCI, the patient suffered recurrent cardiac arrests in the catheterization lab and ICU, ultimately dying from cardiac arrest. This case illustrates the rare but catastrophic progression of STEMI into a dual-vessel event with severe electrical and hemodynamic complications in a young patient. Conclusion: Dual culprit lesions in STEMI can evolve rapidly and unpredictably, particularly in the presence of malignant arrhythmias. Early recognition, rapid intervention, and aggressive hemodynamic support are essential to improve survival in these high-risk cases.